Bruises around the umbilicus in an infant - Sam Hassan; Ghassan Nakib; Mary J. Saviour (MDPI AG, 2016)
The most common causes of umbilical discharge in infancy are infection and umbilical granuloma that may be treated by antibiotics and topical application of silver nitrate subsequently. If the umbilical discharge persists or if there is any abnormal discoloration around the umbilicus, it is important to investigate for underlying congenital abnormality that may be cured by surgical intervention. Unusual presentation of omphalomesenteric duct cyst has been reported in literature. We report, for the first time as far as our search is concerned, a case of a 16-month-old infant who presented initially with persistent umbilical discharge and finally with bruising around the umbilicus in keeping with Cullen's sign. A diagnosis of omphalomesenteric duct cyst containing pancreatic tissue was made on histopathological examination. This case emphasizes that, a persistent umbilical discharge and or discoloration around the umbilicus should be further investigated and an omphalomesenteric duct cyst can present as Cullen's sign.